Apoptosis in the epithelial cells of the rests of Malassez of the periodontium of rat molars - Cerri, Paulo Sérgio [UNESP]; Katchburian, E. (Blackwell Publishing, 2005)
Background and Objectives: Epithelial rests of Malassez are clusters of cells derived from Hertwig's root sheath that remain in the periodontal ligament throughout life. Although it is known that the cells of Malassez proliferate, there are no studies showing that they undergo programmed cell death, i.e. apoptosis. In most tissues, proliferation is balanced by apoptosis. Thus we examined regions of the periodontium of young and adult rat molars in the hope of detecting apoptosis.Methods: Wistar rats aged 29, 45 and 120 days were killed with chloral hydrate (600 mg/kg). Fragments containing maxillary molars were removed and fixed in formaldehyde, decalcified, and embedded in paraffin and glycol methacrylate. Sections were stained with hematoxylin/eosin and the Terminal deoxynucleotidyl transferase-mediated dUTP Nick End Labeling (TUNEL) method for detection of apoptosis. Specimens were also fixed in glutaraldehyde-formaldehyde, decalcified and processed for transmission electron microscopy.Results: Epithelial rests of Malassez containing round/ovoid basophilic dense bodies and TUNEL-positive structures were found in all specimens examined. Ultrastructural examination revealed that some cells of Malassez contained masses of condensed peripheral chromatin and a shrunken cytoplasm exhibiting intact organelles - images typical of apoptosis. Moreover, round/ovoid electron-opaque structures appeared to be in the process of being engulfed by neighboring epithelial cells of Malassez.Conclusions: Our results demonstrate that epithelial cells of Malassez's rests undergo apoptosis in the developing and adult periodontium. Apoptosis may, together with proliferation, be part of the mechanism of turnover/remodelling of the cells of Malassez.
Keywords: apoptosis; epithelial cells; periodontium; rests of Malassez